2006
DOI: 10.1186/1471-2334-6-158
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activity of terpinen-4-ol, the main bioactive component of Melaleuca alternifolia Cheel (tea tree) oil against azole-susceptible and -resistant human pathogenic Candida species

Abstract: Background: Recent investigations on the antifungal properties of essential oil of Melaleuca alternifolia Cheel (Tea Tree Oil, TTO) have been performed with reference to the treatment of vaginal candidiasis. However, there is a lack of in vivo data supporting in vitro results, especially regarding the antifungal properties of TTO constituents. Thus, the aim of our study was to investigate the in vitro and the in vivo anti-Candida activity of two critical bioactive constituents of TTO, terpinen-4-ol and 1,8-cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 21 publications
12
132
1
6
Order By: Relevance
“…This could be induced by ROS generation and autophagosomal enzymes, such as cathepsin but further study is needed to elucidate this hypothesis. It has also been reported that Bcl-2 family proteins might interact with the autophagic proteins (ATGs) or Beclin-1 to turn on/off or switch the mode of cell deaths between apoptosis and autophagic cell death (Nishida et al, 2008;Kang et al, 2011;Fiorini et al, 2013;Naves et al, 2013). ATG5 also plays as a switch on autophagy to apoptosis (Yousefi et al, 2006) and JNK regulates dissociation of Bcl-2 and Beclin-1 (Wei et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be induced by ROS generation and autophagosomal enzymes, such as cathepsin but further study is needed to elucidate this hypothesis. It has also been reported that Bcl-2 family proteins might interact with the autophagic proteins (ATGs) or Beclin-1 to turn on/off or switch the mode of cell deaths between apoptosis and autophagic cell death (Nishida et al, 2008;Kang et al, 2011;Fiorini et al, 2013;Naves et al, 2013). ATG5 also plays as a switch on autophagy to apoptosis (Yousefi et al, 2006) and JNK regulates dissociation of Bcl-2 and Beclin-1 (Wei et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Terpinen-4-ol has many pharmacological activities such as anti-inflammation (Hart et al, 2000;Jeenapongsa et al, 2003), and anti-hypersensitivity (Lahlou et al, 2003). Furthermore, bactericidal (Loughlin et al, 2008) and antifungal properties (Mondello et al, 2006) have also been found in terpinen-4-ol. Moreover, cytotoxicity of terpinen-4-ol on cancer cell lines, e.g., melanoma, has been reported (Calcabrini et al, 2004); which potently induces cell cycle arrest, apoptosis and necrotic cell death (Greay et al, 2010).…”
Section: Terpinen-4-ol Induces Autophagic and Apoptotic Cell Death Inmentioning
confidence: 99%
“…Patompong Khaw-on, Ratana Banjerdpongchai* (Lahlou et al, 2003), anti-bacterial (Loughlin et al, 2008) and anti-fungal infection (Mondello et al, 2006). Furthermore, it can impair the growth of human M14 melanoma cells (Calcabrini et al, 2004) as well as induces necrotic cell death coupled with apoptotic cell death and arrests cell cycle at G1 stage in mouse malignant mesothelioma AE17 and murine melanoma B16-F10 cells (Greay et al, 2010).…”
Section: Induction Of Intrinsic and Extrinsic Apoptosis Pathways In Tmentioning
confidence: 99%
“…9 Besides, the essential oils of M. alternifolia and related species exhibit activity against herpes simplex virus (HSV), causal agent of labial herpes. 10 The oil is also used for treatment of human melanoma, 11 insect bites, skin infections, 12 subcutaneous infections caused by fungi, 13 oral and genital candidiasis, 14 treatment of methicillin-resistant Staphylococcus aureus 15 and respiratory infections. 16 These volatile oils are widely used in industry due to their broad-spectrum of antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%